Analisis Kualitatif Kompetensi, Tantangan, dan Dukungan Guru Pendamping Khusus dalam Implementasi Pendidikan Inklusif di Indonesia - Vicky Purwadi Putra Sawaludin; Lika Hestyaningsih (Jurnal Pendidikan Kebutuhan Khusus, 2026)
This study aims to analyze the competencies, challenges, and institutional support of Special Education Support Teachers (Guru Pendamping Khusus/GPK) in implementing inclusive education in Indonesia. A qualitative approach was employed through a systematic literature review (SLR) of 10 relevant articles and semi‑structured interviews with five active GPKs working in inclusive schools. Data analysis followed Miles & Huberman’s model of reduction, display, and conclusion drawing. Findings reveal that GPK competencies encompass pedagogical, professional, social, and personal dimensions, yet vary in quality, particularly in assessment skills and individualized learning plans. Key challenges include unclear employment status with most GPKs working as contract or honorary staff, high student‑teacher ratios, limited continuous training, and persistent societal stigma toward children with special needs. Institutional support, such as school leadership, government regulation, and adaptive facilities, proved crucial for effective inclusion. In conclusion, the success of inclusive education depends not only on individual GPK competencies but also on systemic support ecosystems. The study implies the need for competency‑based recruitment policies, GPK certification, continuous professional development, and social advocacy to reduce stigma against children with special needs.